Silver Nanoparticle-Based Therapy: Can It Be Useful to Combat Multi-Drug Resistant Bacteria? - Eva M. Mateo; Misericordia Jiménez (MDPI AG, 2022)
The present review focuses on the potential use of silver nanoparticles in the therapy of diseases caused by antibiotic-resistant bacteria. Such bacteria are known as "superbugs", and the most concerning species are Acinetobacter baumannii, Pseudomonas aeruginosa, Staphylococcus aureus (methicillin and vancomycin-resistant), and some Enterobacteriaceae. According to the World Health Organization (WHO), there is an urgent need for new treatments against these "superbugs". One of the possible approaches in the treatment of these species is the use of antibacterial nanoparticles. After a short overview of nanoparticle usage, mechanisms of action, and methods of synthesis of nanoparticles, emphasis has been placed on the use of silver nanoparticles (AgNPs) to combat the most relevant emerging resistant bacteria. The toxicological aspects of the AgNPs, both in vitro using cell cultures and in vivo have been reviewed. It was found that toxic activity of AgNPs is dependent on dose, size, shape, and electrical charge. The mechanism of action of AgNPs involves interactions at various levels such as plasma membrane, DNA replication, inactivation of protein/enzymes necessary, and formation of reactive oxygen species (ROS) leading to cell death. Researchers do not always agree in their conclusions on the topic and more work is needed in this field before AgNPs can be effectively applied in clinical therapy to combat multi-drug resistant bacteria.